Resistant Against De-depression: LTD-Like Plasticity in the Human Motor Cortex Induced by Spaced cTBS - Goldsworthy, Mitchell R; Müller-Dahlhaus, Florian; Ridding, Michael C; Ziemann, Ulf (Cerebral cortex (New York, N.Y. 1991), 2015)
The long-term depression (LTD)-like changes in human primary motor cortex (M1) excitability induced by continuous theta burst stimulation (cTBS) are subject to reversal (i.e., de-depression) following behavioral engagement of M1, limiting its therapeutic potential under behaviorally relevant conditions. Experiments in animals suggest that the repeated, spaced application of stimulation trains may consolidate synaptic plasticity, making it resistant to reversal by physiological activity. Although there is evidence that repeated cTBS prolongs LTD-like M1 neuroplasticity in humans, whether these effects are resistant to de-depression has not been tested. We investigated whether the neuroplastic effects of paired cTBS trains were resistant to de-depression by a sustained, submaximal voluntary contraction of the hand muscles. In the absence of cTBS, voluntary contraction had no effect on motor evoked potentials (MEPs) recorded from the right first dorsal interosseous muscle. While the LTD-like MEP depression induced by a single cTBS was abolished by subsequent voluntary contraction, paired cTBS induced MEP depression that was resistant to reversal. This MEP depression was also resistant to reversal when an experimental de-depression protocol was used instead of a voluntary contraction. Our findings suggest that repeated cTBS applications consolidate LTD-like M1 neuroplasticity, which may have important implications for the clinical application of cTBS.